2009
DOI: 10.1021/cg9001779
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Crystalline TiO2by Plasma Enhanced Chemical Vapor Deposition

Abstract: TiO 2 thin films in the form of anatase have been prepared by plasma enhanced chemical vapor deposition (PECVD) at 523 K as the substrate temperature and a low working pressure. The study of the microstructure and texture of the films at different stages of deposition show that their growth follows the Kolmogorov's model developed to describe the evolution of crystalline films from a saturated homogeneous medium. An additional characteristic feature of the growth process by PECVD is the formation of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 52 publications
2
58
0
Order By: Relevance
“…Thus, for example, either columnar or homogeneous TiO 2 thin films can be obtained by using pure O 2 or a mixture Ar+O 2 as plasma gas, respectively [55][56][57]. The formation of homogeneous thin film microstructures by PECVD has been associated with a growing mechanism where surface diffusion of ad-species is the controlling process [55][56][57], while the columnar growth has been related with the existence of shadowing effects and a high sticking coefficient of the ad-species coming from the plasma [55,56,60]. In connection with this columnar growth of thin films, it has been realized that in PECVD processes the particles arrive with a wide distribution of incoming angles and that the actual angular distribution is a key factor in determining the microstructure developed by the films [58,59].…”
Section: 1columnar Thin Films Of Tio 2 and Zno On Flat And Non-metamentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, for example, either columnar or homogeneous TiO 2 thin films can be obtained by using pure O 2 or a mixture Ar+O 2 as plasma gas, respectively [55][56][57]. The formation of homogeneous thin film microstructures by PECVD has been associated with a growing mechanism where surface diffusion of ad-species is the controlling process [55][56][57], while the columnar growth has been related with the existence of shadowing effects and a high sticking coefficient of the ad-species coming from the plasma [55,56,60]. In connection with this columnar growth of thin films, it has been realized that in PECVD processes the particles arrive with a wide distribution of incoming angles and that the actual angular distribution is a key factor in determining the microstructure developed by the films [58,59].…”
Section: 1columnar Thin Films Of Tio 2 and Zno On Flat And Non-metamentioning
confidence: 99%
“…shown that the thin film microstructure is affected not only by shadowing, diffusion or other similar processes, but mainly by the dynamics of formation of crystallites [60].…”
Section: 1columnar Thin Films Of Tio 2 and Zno On Flat And Non-metamentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26] In selecting an appropriate deposition technology for this specific application, several criteria have to be considered such as coating morphology, deposition rate and coverage, interfacial quality, and industrial applicability. Among these methods, the ALD process is based on the sequential use of self-terminating surface reactions, which is perfect for the deposition of metal oxide layers with atomic layer control on geometrical nanostructures with high aspect ratios.…”
mentioning
confidence: 99%
“…19 It is important to address that the temperature required for the formation of the anatase layer (250 ºC) is close to the sublimation temperature of the H 2 PC small-molecule. Therefore, the direct deposition of the TiO 2 at 250 ºC on the ONWs used as 1D scaffolds would eventually lead to their sublimation and evacuation.…”
Section: Fabrication Of Anatase Hierarchical Nanotubesmentioning
confidence: 99%